Enzymatic properties of alcohol dehydrogenase PedE_M.s. derived from Methylopila sp. M107 and its broad metal selectivity - Xiao, Ying; Wu, Kaijuan; Batool, Syeda Sundas; Wang, Qingqun; Chen, Hao; Zhai, Xingyu; Yu, Zheng; Huang, Jing (Frontiers in Microbiology, 2023)
As an important metabolic enzyme in methylotrophs, pyrroloquinoline quinone (PQQ)-dependent alcohol dehydrogenases play significant roles in the global carbon and nitrogen cycles. In this article, a calcium (Ca 2+ )-dependent alcohol dehydrogenase PedE_M.s., derived from the methylotroph Methylopila sp. M107 was inserted into the modified vector pCM80 and heterologously expressed in the host Methylorubrum extorquens AM1. Based on sequence analysis, PedE_M.s., a PQQdependent dehydrogenase belonging to a methanol/ethanol family, was successfully extracted and purified. Showing by biochemical results, its enzymatic activity was detected as 0.72 U/mg while the Km value was 0.028 mM while employing ethanol as optimal substrate. The activity of PedE_M.s. could be enhanced by the presence of potassium (K + ) and calcium (Ca 2+ ), while acetonitrile and certain common detergents have been found to decrease the activity of PedE_M.s.. In addition, its optimum temperature and pH were 30 °C and pH 9.0, respectively. Chiefly, as a type of Ca 2+dependent alcohol dehydrogenase, PedE_M.s. maintained 60-80% activity in the presence of 10 mM lanthanides and displayed high affinity for ethanol compared to other PedE-type enzymes. The 3D structure of PedE_M.s. was predicted by AlphaFold, and it had an 8-bladed propeller-like superbarrel. Meanwhile, we could speculate that PedE_M.s. contained the conserved residues Glu213, Asn300, and Asp350 through multiple sequence alignment by Clustal and ESpript. The analysis of enzymatic properties of PedE_M.s. enriches our knowledge of the methanol/ethanol family PQQ-Enzymatic properties of PedE_M.s.2 dependent dehydrogenase. This study provides new ideas to broaden the application of alcohol dehydrogenase in alcohol concentration calculation, biosensor preparation, and other industries.